Ensuring Quality Education and Good Learning Environments for Students: Improving the quality of higher education through good teaching practices - Bernardo, Ana B.; Castro-López, Adrián; Almeida, Leandro; Rivas, Sílvia F. (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The ever-growing information and communications within society require us to continuously update our knowledge. For this reason, higher education must provide students and lecturers with the opportunity to implement new learning approaches in the classroom. In this sense, teaching is adapting to a fast-changing world, and achieving a high-quality standard for our educational systems will ensure that the education standard appropriately adapts to both the current times and to new teaching-learning processes. This topic captures the attention of different socio-educational actors in order to achieve an education style that develops individuals and provides them with the necessary strategies to assist their learning throughout their lifetime.